The Global Macroeconomic Burden of Breast Cancer: Implications for Oncologic Surgery. Issue 6 (December 2021) - Ranganathan, Kavitha; Singh, Puneet; Raghavendran, Krishnan; Wilkins, Edwin G.; Hamill, Jennifer B.; Aliu, Oluseyi; Newman, Lisa A.; Hutton, David; Momoh, Adeyiza O.
Abstract : Objective: In this study, we quantified the global macroeconomic burden of breast cancer to underscore the critical importance of improving access to oncologic surgical care internationally. Summary Background Data: Breast cancer mortality in many low and middle-income countries (LMICs) is dramatically higher than in high-income countries. Prior to identifying solutions, however, it is important to first define the burden of disease. Methods: Data from the Institute of Health Metrics and Evaluation (2005–2015) were used to assess epidemiologic trends for 194, middle, and low-income countries. Economic burden defined by Welfare Loss (WL) was calculated by measuring disability-adjusted-life-years lost to breast cancer alongside the dollar equivalent of a value of statistical life year and as a function of each country's gross domestic product (GDP). Results: Annual mortality rates among breast cancer patients were significantly greater in LMICs in South Asia (3.06 per 100 women) and Sub-Saharan Africa (2.76 per 100 women), compared with high-income countries like the United States (1.69 per 100 women). From 2005–2015, mortality in South Asia increased by 8.20% and decreased by 6.45% in Sub-Saharan Africa; mortality rates in 2015 were observed as 27.9 per 100, 000 in South Asia and 18.61 per 100, 000 in Sub-Saharan Africa. Countries in South Asia demonstrated the greatest rise in WL due to breast cancer, from 0.05% to 0.08% of GDP. Conclusions: The burden of disease and economic impact of breast cancer is intensifying in LMICs. Global efforts to improve access to surgical care for women with breast cancer could reduce mortality and mitigate the social and financial impact of this disease in LMICs. Abstract : Supplemental Digital Content is available in the text